Influence of Phase-Change Materials on Thermo-Physiological Comfort in Warm Environment. (23rd April 2013) - Celcar, Damjana
Abstract : The purpose of this research work is to investigate the influence of phase-change materials (PCMs) on thermo-physiological comfort of different male business clothing systems evaluated in warm environment. The impact of particular business clothing on the thermo-physiological comfort of the wearer during different physical activity and environmental conditions (between 25°C and 10°C with step of 5°C), artificially created in a climate chamber, was determined experimentally, as a change of three physiological parameters of a human being: mean skin temperature, heart rate, and the amount of evaporated and condensed sweat. A questionnaire and an assessment scale were also used before, during, and after each experiment in order to evaluate the wearer's subjective feeling of comfort. The results of the performed research work show that male business clothing systems in combination with PCMs do not affect the thermal-physiological comfort of the wearer in warm environment significantly, except at an ambient temperature of 15°C, where clothing systems in combination with PCMs produce a small heating effect. Furthermore, it was concluded that clothing systems in combination with PCMs indicate a small temporary thermal effect that is reflected in a slight rising or lowering of mean skin temperature during activity changes.